Case Report: Rare Presentation of Rapid Progressive Osteoarthritis of the Hip - Tolga Tolunay; Orkun Büyüksayın; Hakan Atalar; Alimcan Baymurat; Asım Ahmadov (Gazi Medical Journal)
Rapidly progressive osteoarthritis (OA) of the hip is a rare and incompletely understood disorder with scarce literature about variations in natural history within a population. The patient presented with rapidly progressive hip pain and stiffness with limited range of motion. Imaging studies revealed severe OA of the hip joint with significant joint space narrowing and osteophyte formation. Conservative management with pain medications and physical therapy was attempted, but failed to provide significant relief. The patient ultimately underwent total hip arthroplasty, with successful resolution of symptoms and return to normal activities.